Genome sequence and description of Timonella senegalensis gen. nov., sp. nov., a new member of the suborder Micrococcinae. Issue 2 (March 2013) - Mishra, Ajay; Lagier, Jean-Christophe; Robert, Catherine; Raoult, Didier; Fournier, Pierre-Edouard
Abstract Timonella senegalensis strain JC301T gen. nov., sp. nov. is the type strain ofT. senegalensis gen. nov., sp. nov., a new species within the newly proposed genusTimonella . This bacterial strain was isolated from the fecal flora of a healthy Senegalese patient. In this report, we detail the features of this organism, together with the complete genome sequence and annotation.Timonella senegalensis strain JC301T exhibits the highest 16S rRNA similarity (95%) withSanguibacter marinus, the closest validly published bacterial species. The genome ofT. senegalensis strain JC301T is 3, 010, 102-bp long, with one chromosome and no plasmid. The genome contains 2, 721 protein-coding genes and 72 RNA genes, including 5 rRNA genes. The genomic annotation revealed thatT. senegalensis strain JC301T possesses the complete complement of enzymes necessary for thede novo biosynthesis of amino acids and vitamins (except for riboflavin and biotin), as well as the enzymes involved in the metabolism of various carbon sources, chaperone genes, and genes involved in the regulation of polyphosphate and glycogen levels.